Model efektifitas keuangan dana darurat dalam mendorong pemulihan ekonomi warga desa Ciherang pasca bencana alam gempa Cianjur - Maulana Malik Muhammad; Vicky Septian Rachman (LPMP Imperium, 2025)
This research examines the management of emergency funds in post-earthquake recovery in Ciherang Village, Cianjur, focusing on challenges in fund distribution. Key issues include bureaucratic delays, poor inter-agency coordination, and inadequate fund allocation compared to actual needs. Administrative hurdles, such as lost documents and lengthy verification, cause significant delays in disbursement. Allocated funds often fail to cover the full extent of damage, forcing residents to seek additional resources for repairs or livelihood restoration. Poor coordination between agencies and unclear bureaucratic processes exacerbate inefficiencies and frustration among affected populations. Many struggle to navigate a system lacking transparency, further hindering recovery efforts. The study highlights the need for reforms to simplify procedures, improve coordination, and align fund allocation with real needs. Such improvements are essential to accelerate recovery and effectively support disaster-affected communities, ensuring timely assistance and reducing financial strain on survivors. Public interest statements The study focuses on the importance of emergency fund management in post-disaster recovery. It identifies challenges related to fund allocation and bureaucratic delays and advocates for streamlined processes to provide timely assistance to affected communities. Improved coordination and efficient use of emergency funds can reduce recovery time and financial strain for disaster victims, leading to faster restoration of livelihoods and infrastructure.